Effects of the Addition of Moringa oleifera Leaf Meal to a Ration Containing Rice Hull Supplemented with Starpig on the Production Performance and Nutritional Content of Eggs of Bali Duck - Trisnadewi , Anak Agung Ayu Sri; Partama, Ida Bagus Gaga; Yadnya, Tjokorda Gede Belawa (International Journal of Poultry Science, 2020)
Objectives: This study aimed to determine the effects of the addition of Moringa oleifera leaf meal to a ration containing rice hull supplemented with starpig on the production performance and nutritional content of egg of Bali duck. Materials and Methods: This study used a completely randomized design (CRD). The four treatments included control ration A = ration without rice hull, Moringa oleifera leaf meal and starpig, B = ration containing 10% rice hull, C = ration containing 10% rice hull and 1% Moringa oleifera leaf meal and D = ration containing 10% rice hull, 1% Moringa oleifera leaf meal and 1% starpig. Each treatment consisted of four replicates and each replicate contained three female Bali ducks with homogeneous body weight. The variables observed included the production performance and nutritional content of egg of Bali duck, which were based on feed consumption, feed antioxidant consumption, final body weight, water content, protein content, fat content and total cholesterol. Results: Treatment B increased ration consumption and treatments C and D did not affect ration consumption compared with that after treatment A. Antioxidant consumption was the highest for treatment D. Treatment D also increased the egg protein content, reduced the fat content and total cholesterol of eggs and had no effect on the water content compared with those after treatment A. Conclusion: Moringa oleifera leaf meal in a ration containing rice hull supplemented with starpig improves production performance and nutritional content of egg of Bali duck.